Brain energy metabolism: a roadmap for future research - Rae, Caroline; Baur, Joseph A.; Borges, Karin; Dienel, Gerald; Díaz-García, Carlos Manlio; Douglass, Starlette R.; Drew, Kelly; Duarte, João M. N.; Duran, Jordi; Kann, Oliver; Kristian, Tibor; Lee-Liu, Dasfne; et al. (Journal of neurochemistry, 2024)
Although we have learned much about how the brain fuels its functions over the last decades, there remains much still to discover in an organ that is so complex. This article lays out major gaps in our knowledge of interrelationships between brain metabolism and brain function, including biochemical, cellular, and subcellular aspects of functional metabolism and its imaging in adult brain, as well as during development, aging, and disease. The focus is on unknowns in metabolism of major brain substrates and associated transporters, the roles of insulin and of lipid droplets, the emerging role of metabolism in microglia, mysteries about the major brain cofactor and signaling molecule NAD+, as well as unsolved problems underlying brain metabolism in pathologies such as traumatic brain injury, epilepsy, and metabolic downregulation during hibernation. It describes our current level of understanding of these facets of brain energy metabolism as well as a roadmap for future research.
Zuerst veröffentlicht: 06. Januar 2024
Gesehen am 05.08.2024